The danger of disembodied humanity - Horchak, O. V. (AI and Society, 2026)
For centuries, philosophers have been fascinated by the idea of a mind detached from the body. In the Phaedo, Plato envisioned the soul as the pinnacle of intellect free from its mortal shell. Centuries later, Descartes crystallized this dualistic obsession in his famous declaration “I think, therefore I am”, defining thought as the very essence of being, independent of the physical body. In the twentieth century, this ancient longing for disembodied thinking found new scientific expression in the cognitive revolution of the 1950s. As George A. Miller observed in his 2003 paper in Trends in Cognitive Sciences, this revolution “restored cognition to scientific respectability,” forging an interdisciplinary foundation that unified fields like psychology, linguistics, neuroscience, computer science, anthropology, and philosophy. By proposing that computational processes could simulate human cognition, it laid the groundwork for modern artificial intelligence (AI). Today’s large language models, like ChatGPT, stand as the latest culmination of humanity’s centuries-long quest for disembodied thought.